2015
DOI: 10.1177/0022022115611749
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Psychological Atlas of the World With Mixture Modeling

Abstract: This article presents findings based on the outcomes of research conducted with 8,883 participants from 33 countries. It employs mixture modeling (latent profile analysis) to classify countries into latent classes. The country-level analyses are based on three social attitudes factor scores of Nastiness, Religiosity, and Morality. The results indicate that the main sources of cross-cultural differences are with respect to a broadly defined Conservatism/Liberalism. Three groups of societies—that is, “psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Thus, the LAMBI subscales have good stability and test-retest reliability. or from various papers (e.g., Muthen, 2002;Stankov & Lee, 2016). We found that the best fitting model (in bold) yielded four profile groups as shown in Table 5.…”
Section: Supplement To Study 3: Test-retest Reliability Of the Five Fmentioning
confidence: 78%
“…Thus, the LAMBI subscales have good stability and test-retest reliability. or from various papers (e.g., Muthen, 2002;Stankov & Lee, 2016). We found that the best fitting model (in bold) yielded four profile groups as shown in Table 5.…”
Section: Supplement To Study 3: Test-retest Reliability Of the Five Fmentioning
confidence: 78%
“…Furthermore, the overreliance on U.S. samples and political ideologies is now beginning to be complemented by studies examining how moral concerns may be similar or different in different cultural and political contexts (e.g., Nilson, & Strupp-Levitsky, 2016). Recent work has compared the moral foundations endorsed by Chinese versus U.S. samples (Kwan, 2016), has examined this among Muslims in Turkey (Yilmaz, Harma, & Bakçekapili, & Cesur, 2016), and has made other intercultural comparisons (Stankov & Lee, 2016a, 2016b; Sullivan, Stewart, Landau, Liu, Yang, & Diefendorf, 2016). This helps understand that some moral concerns emerge consistently across different cultural contexts, and the macro-level cultural values and corruption indicators that characterize them (Mann, Garcia-Rada, Hornuf, Tafurt, & Ariely, 2016).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…A typical finding is that, for the same variables, the correlations among the countries are higher than among the individuals. Consequently, at the country-level, a strong social Conservatism factor tends to appear implying that instead of being unrelated, Morality and Nastiness, together with Religiosity, define the same Conservative Syndrome (see Stankov & Lee, 2016b).…”
Section: Country-level Conservative Syndromementioning
confidence: 99%